Digitalizing the Clinical Research Informed Consent Process: Assessing the Participant Experience in Comparison With Traditional Paper-Based Methods. Issue 3 (19th March 2023) - Buckley, Michael T.; O'Shea, Molly R.; Kundu, Sangeeta; Lipitz-Snyderman, Allison; Kuperman, Gilad; Shah, Suken; Iasonos, Alexia; Houston, Collette; Terzulli, Stephanie L.; Lengfellner, Joseph M.; Sabbatini, Paul
Abstract : PURPOSE: Consent processes are critical for clinical care and research and may benefit from incorporating digital strategies. We compared an electronic informed consent (eIC) option to paper consent across four outcomes: (1) technology burden, (2) protocol comprehension, (3) participant agency (ability to self-advocate), and (4) completion of required document fields. METHODS: We assessed participant experience with eIC processes compared with traditional paper-based consenting using surveys and compared completeness of required fields, over 3 years (2019-2021). Participants who consented to a clinical trial at a large academic cancer center via paper or eIC were invited to either pre-COVID-19 pandemic survey 1 (technology burden) or intrapandemic survey 2 (comprehension and agency). Consent document completeness was assessed via electronic health records. RESULTS: On survey 1, 83% of participants (n = 777) indicated eIC was easy or very easy to use; discomfort with technology overall was not correlated with discomfort using eIC. For survey 2, eIC (n = 262) and paper consenters (n = 193) had similar comprehension scores. All participants responded favorably to at least five of six agency statements; however, eIC generated a higher proportion of positive free-text comments ( P < .05), with themes such as thoroughness of the discussion and consenter professionalism. eIC use yielded no completeness errors across 235 consents versus 6.4% for paper ( P < .001). CONCLUSION: Our findings suggest that eIC when compared with paper (1) did not increase technology burden, (2) supported comparable comprehension, (3) upheld key elements of participant agency, and (4) increased completion of mandatory consent fields. The results support a broader call for organizations to offer eIC for clinical research discussions to enhance the overall participant experience and increase the completeness of the consent process.